Ganoderma lucidum Spore Polysaccharide Inhibits the Growth of Hepatocellular Carcinoma Cells by Altering Macrophage Polarity and Induction of Apoptosis - Ming Song; Zhen-hao Li; Hong-shun Gu; Ru-ying Tang; Rui Zhang; Ying-li Zhu; Jin-lian Liu; Jian-jun Zhang; Lin-yuan Wang (Journal of Immunology Research)
Background. Ganoderma lucidum has certain components with known pharmacological effects, including strengthening immunity and anti-inflammatory activity. G. lucidum seeds inherit all its biological characteristics. G. lucidum spore polysaccharide (GLSP) is the main active ingredient to enhance these effects. However, its specific biological mechanisms are not exact. Our research is aimed at revealing the specific biological mechanism of GLSP to enhance immunity and inhibit the growth of H22 hepatocellular carcinoma cells. Methods. We extracted primary macrophages (Mø) from BALB/c mice and treated them with GLSP (800 μg/mL, 400 μg/mL, and 200 μg/mL) to observe its effects on macrophage polarization and cytokine secretion. We used GLSP and GLSP-intervened macrophage supernatant to treat H22 tumor cells and observed their effects using MTT and flow cytometry. Moreover, real-time fluorescent quantitative PCR and western blotting were used to observe the effect of GLSP-intervened macrophage supernatant on the PI3K/AKT and mitochondrial apoptosis pathways. Results. In this study, GLSP promoted the polarization of primary macrophages to M1 type and the upregulation of some cytokines such as TNF-α, IL-1β, IL-6, and TGF-β1. The MTT assay revealed that GLSP+Mø at 400 μg/mL and 800 μg/mL significantly inhibited H22 cell proliferation in a dose-dependent manner. Flow cytometry analysis revealed that GLSP+Mø induced apoptosis and cell cycle arrest at the G2/M phase, associated with the expression of critical genes and proteins (PI3K, p-AKT, BCL-2, BAX, and caspase-9) that regulate the PI3K/AKT pathway and apoptosis. GLSP reshapes the tumor microenvironment by activating macrophages, promotes the polarization of primary macrophages to M1 type, and promotes the secretion of various inflammatory factors and cytokines. Conclusion. Therefore, as a natural nutrient, GLSP is a potential agent in hepatocellular carcinoma cell treatment and induction of apoptosis.